Legal Diversity in the Concept of ‘Iddah: Comparative Analysis among Shafi’i, Maliki, Hanafi, and Hanbali Schools - Kummil Lailaturrohmah (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
This study examines the concept of ‘iddah (waiting period) within Islamic family law through a comparative analysis of the four Sunni schools—Shafi’i, Maliki, Hanafi, and Hanbali. Rooted in the Qur’an and Sunnah, ‘iddah serves multiple juridical and ethical purposes, including the preservation of lineage (ḥifẓ al-nasab), clarification of paternity, and maintenance of moral and social order following marital dissolution. Despite unanimous recognition of its obligation, the four schools exhibit methodological diversity in interpreting its duration, commencement, and conditions. This research, employing a qualitative, doctrinal, and comparative approach (fiqh muqāran), reveals that juristic differences arise from linguistic ambiguities, contextual considerations, and distinctive uṣūl al-fiqh methodologies—textualism, rational analogy, or welfare-based reasoning. Rather than reflecting contradiction, such ikhtilāf (diversity) demonstrates the epistemic richness and adaptability of Islamic law. The findings underscore that all schools converge on shared maqāṣid al-sharī‘ah—justice, lineage protection, and compassion—while differing in procedural applications. The study concludes that recognizing classical pluralism can inform contemporary legal codifications and family law reforms in Muslim societies. It affirms that the vitality of Islamic jurisprudence lies in harmonizing unity of purpose with diversity of interpretation, ensuring Sharia’s continued relevance in evolving social contexts.